2020
DOI: 10.1088/2053-1591/ab619e
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of optical, mechanical and nonlinear properties of potassium acid phthalate single crystal: a potential candidate for optoelectronic applications

Abstract: A good optical quality semi-organic single crystal of Potassium Acid Phthalate (KAP) was harvested from aqueous solution by using slow evaporation solution growth technique (SEST) at ambient condition. The defect free single crystal of KAP was analyzed by different instrumentation techniques, for checking its compatibility for different applications. Its unit cell dimensions and phase purity was examined by powder X-ray diffraction (PXRD) and found that it crystallizes in orthorhombic with non-centrosymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Optical transparency of a material and a wide optical band gap (E g ) in the visible spectrum are the two foremost parameters for laser applications (Kumari et al, 2020a;Bhat & Dharmaprakash, 2002). A cut and well polished single crystal of EPHB with a thickness t = 0.2 cm was subjected to UVvisible analysis to examine its optical behaviour.…”
Section: Transmission Spectrum and Optical Band Gapmentioning
confidence: 99%
“…Optical transparency of a material and a wide optical band gap (E g ) in the visible spectrum are the two foremost parameters for laser applications (Kumari et al, 2020a;Bhat & Dharmaprakash, 2002). A cut and well polished single crystal of EPHB with a thickness t = 0.2 cm was subjected to UVvisible analysis to examine its optical behaviour.…”
Section: Transmission Spectrum and Optical Band Gapmentioning
confidence: 99%
“…Nonlinear organic and semiorganic single crystals are widely used in different scientific and technological applications due to their efficacy in generating second-order harmonics for various lasers source. [1][2][3][4] Recent decades have shown that such single crystals are capable of producing second harmonics due to their non-centrosymmetric nature and are also potential candidates for the generation and detection of terahertz (THz) waves, 5 which are considered to represent a bridge between optical waves, i.e., infrared, and microwaves in the electromagnetic (EM) spectrum with frequencies generally in the range from 100 GHz to 10 THz. Radiation in the terahertz region is very useful for producing images in various fields such as medical, defense, and security.…”
Section: Introductionmentioning
confidence: 99%